New insight to the characteristics and clinical course of clusters of patients with imaging confirmed disc‐related sciatica. (21st October 2019) - Stynes, Siobhán; Grøvle, Lars; Haugen, Anne Julsrud; Konstantinou, Kika; Grotle, Margreth
Abstract: Background: Referral to secondary care is common for a considerable proportion of patients with persistent sciatica symptoms. It is unclear if information from clinical assessment can further identify distinct subgroups of disc‐related sciatica, with perhaps different clinical courses. Aims: This study aims to identify and describe clusters of imaging confirmed disc‐related sciatica patients using latent class analysis, and compare their clinical course. Methods: The study population were 466 patients with disc‐related sciatica. Variables from clinical assessment were included in the analysis. Characteristics of the identified clusters were described and their clinical course over 2 years was compared. Results: A four‐cluster solution was optimal. Cluster 1 (n = 110) had mild back and leg pain; cluster 2 (n = 59) had moderate back and leg pain; cluster 3 (n = 158) had mild back pain and severe leg pain; cluster 4 (n = 139) had severe back and leg pain. Patients in cluster 4 had the most severe profile in terms of disability, distress and comorbidity and the lowest reported global change and the smallest proportion of patients with a successful outcome at 2 years. Of the 135 patients who underwent surgery, 42% and 41% were in clusters 3 and 4, respectively. Conclusions: Using a strict diagnosis of sciatica, this work identified four clusters of patients primarily differentiated by back and leg pain severity. Patients with severe back and leg pain had the most severe profile at baseline and follow‐up irrespective of intervention. This simple classification system may be useful when considering prognosis and management with sciatica patients. Significance: Using data from a large observational prospective study, this work identifies four distinct clusters of patients with imaging confirmed disc‐related sciatica. This classification could be used when considering prognosis and management with sciatica patients at their initial consultation.